2016
DOI: 10.1177/2158244016663609
|View full text |Cite
|
Sign up to set email alerts
|

Australian Technical Teachers’ Experience of Technology Integration in Teaching

Abstract: This study investigated teachers' conceptions of technology integration into their teaching from two renowned technical and vocational education (TVE) institutes in New South Wales, Australia. Thirteen teachers were interviewed using qualitative techniques informed by the phenomenographic approach. The analysis of the data revealed that TVE teachers perceived the use of technology in teaching in four qualitatively different ways: (a) upgrading teacher knowledge, (b) ease of communication, (c) effective teachin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 39 publications
0
18
0
3
Order By: Relevance
“…It can be identified that integrating online learning in business English class provides support for communication and engagement in learning. Based on research, using blended learning brings ease of communication (Khan, Bibi, & Hasan, 2016), which means it can give samples of interaction and exposures to communication anywhere and anytime.…”
Section: Figure 1 the Design Of Blended Learning Instructionmentioning
confidence: 99%
“…It can be identified that integrating online learning in business English class provides support for communication and engagement in learning. Based on research, using blended learning brings ease of communication (Khan, Bibi, & Hasan, 2016), which means it can give samples of interaction and exposures to communication anywhere and anytime.…”
Section: Figure 1 the Design Of Blended Learning Instructionmentioning
confidence: 99%
“…Regarding the use of the software Word and PowerPoint, the analyzed students use these mobile applications to edit and create information in the learning processes, mobile applications whose use is widespread in the majority of students on a daily basis and which has led to changes in traditional teaching methodologies [46,128].…”
Section: Discussionmentioning
confidence: 99%
“…While studies have identified drivers and barriers (e.g., Conole 2016;Porter and Graham 2016), studies exploring reasons for long-term sustained uses have not emerged as frequently (e.g., Mumtaz 2000). Developing effective practitioner enactment (Heitink et al 2016;Khan et al 2016) requires detailed knowledge about relationships of factors and features that enable teachers, trainers, and employees to understand how and why they can use digital technologies in their respective work areas. Features and factors enabling use not only concern professional attitudes and understanding of technological affordances and facilities but also attitudes and understanding towards technologies and, importantly, innovation.…”
Section: Introductionmentioning
confidence: 99%